2008
DOI: 10.1182/blood-2007-12-126888
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell and natural killer cell cross-talk: a pivotal role of CX3CL1 in NK cytoskeleton organization and activation

Abstract: IntroductionNatural killer (NK) cell activation is initiated when NK cells form tight contacts with target cells. [1][2][3][4] However, this activation can be abrogated by interactions between major histocompatibility complex (MHC) class I molecules and inhibitory killer cell immunoglobulin-like receptors (KIRs). SHP-1 is then recruited to the KIR intracytoplasmic domain and a dominant inhibition of cytoskeletal and lipid raft polarization occurs, protecting MHC class I-positive targets from autologous NK cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
52
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 21 publications
2
52
0
Order By: Relevance
“…Studying the response of NK cells to L. monocytogenes, it was demonstrated that both cytokines and cell contact with infected DCs were required for optimal IFN-γ production by NK cells (149). CX3CL1 (fractalkine) expressed on mature DCs is another player in the synapses formed between DCs and NK cells (150). Such contact was visualized by clustering of DCs, not only with NK cells, but also with granulocytes and monocytes/macrophages (151) and involved the priming of NK cells by IFN-α/β and a trans-presentation of IL-15 (147).…”
Section: Nk Cells Within a Cellular Crosstalkmentioning
confidence: 99%
“…Studying the response of NK cells to L. monocytogenes, it was demonstrated that both cytokines and cell contact with infected DCs were required for optimal IFN-γ production by NK cells (149). CX3CL1 (fractalkine) expressed on mature DCs is another player in the synapses formed between DCs and NK cells (150). Such contact was visualized by clustering of DCs, not only with NK cells, but also with granulocytes and monocytes/macrophages (151) and involved the priming of NK cells by IFN-α/β and a trans-presentation of IL-15 (147).…”
Section: Nk Cells Within a Cellular Crosstalkmentioning
confidence: 99%
“…Cancer immunotherapies using DC vaccination now preferably apply mature DCs (mDCs) loaded with tumor-associated Ags, which are injected near or directly into lymph nodes where they interact with naive T cells, thereby fostering activation and differentiation of CD8 + CTLs. In addition, DCs can regulate cytokine polarization of T cells, and some mDCs can activate NK cells, which contribute to innate immune responses that help to orchestrate long-term Ag-specific memory T cell responses (3)(4)(5)(6).…”
mentioning
confidence: 99%
“…They act as sentinels that quickly respond to foreign antigens; when activated, DCs transfer important information about the invading pathogens and the innate response in the periphery to T cells, thus inducing an appropriate adaptive immune response (14). Mature DCs also trigger NK cell effector functions, which promote Th1 polarization (15,16). On the basis of their ability to take up antigens, present the antigens to naive T cells, and activate those T cells, DCs constitute useful tools for assessing lymphocytic induction and polarization after exposure to microorganisms involved in HP.…”
mentioning
confidence: 99%